Multi-Task Collaboration CPS Modeling Based on Immune Feedback - Haiying Li; Chunfang Ding; Shuang Guo; Xiaojing Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In this paper, a dynamic multi-task collaboration CPS control model based on the self-adaptive immune feedback is proposed and implemented in the smart home environment. First, the internal relations between CPS and the biological immune system are explored via their basic theories. Second, CPS control mechanism is elaborated through the analysis of CPS control structure. Finally, a comprehensive strategy for support is introduced into multi-task collaboration to improve the dynamic cognitive ability. At the same time, the performance of parameters is correspondingly increased by the operator of the antibody concentration and the selective pressure. Furthermore, the model has been put into service in the smart home laboratory. The experimental results show that this model can integrate user’s needs into the environment for properly regulating the home environment. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3633